Innovative Mucoadhesive Precursor of Liquid Crystalline System Loading Anti-Gellatinolytic Peptide for Topical Treatment of Oral Cancer - Calixto, Giovana Maria Fioramonti [UNESP]; Victorelli, Francesca Damiani [UNESP]; Franz-Montan, Michelle; Baltazar, Fatima; Chorilli, Marlus [UNESP] (Amer Scientific Publishers, 2021)
Current researches report an actual benefit of a treatment for oral cancer via inhibition of proteolytic matrix metalloproteinases (MPP) with a peptide drug, called CTT1. However, peptides present poor oral bioavailability. Topical administration on oral mucosa avoids its passage through the gastrointestinal tract and the first-pass liver metabolism, but the barrier function of the oral mucosa can impair the permeation and retention of CTT1. The objective of this study is to incorporate CTT1 into a mucoadhesive precursor of liquid crystalline system (PLCS) as an interesting strategy for the topical treatment of oral cancer. PLCS consisting of oleic acid, ethoxylated 20 and propoxylated cetyl alcohol 5, polyethyleneimine (P)-associated chitosan (C) dispersion and CTT1 (FPC-CTT1) was developed and characterized by polarized light microscopy (PLM) and small-angle X-ray scattering (SAXS). In vitro permeation and retention across esophageal mucosa, in vitro cytotoxicity towards tongue squamous cell carcinoma cells, and in vivo evaluation of vascular changes using the chick embryo chorioallantoic membrane (CAM) model were performed. PLM and SAXS showed that FPC-CTT1acted as PLCS, because it formed a lamellar liquid crystalline system after the addition of artificial saliva. FPC-CTT1increased approximately 2-fold the flux of permeation and 3- fold the retention of CTT1 on the porcine esophageal mucosa. CTT1 does not affect cell viability. CAM tests showed that FPC preserved the blood vessels and it can be a safe formulation. These findings encourage the use of the FPC-CTT1 for topical treatment of oral cancer.
Keywords: Pharmaceutical Nanotechnology; Drug Delivery Systems; Liquid Crystalline System; Peptide Drug; Oral Cancer